Tingkat Pengetahuan dan Sikap Sebelum dan Setelah Penyuluhan tentang PHBS pada Siswa SD Negeri 13 Blang Mangat - Mauliza; Aprillya, Asri; Khairunnisa, Cut (Jurnal Ilmiah Manusia Dan Kesehatan, 2023)
Healthy Lifestyle is one of the main focuses that the government pays attention to in improving the health status of the Indonesian people. There needs to be a behavior change to improve this Healthy Lifestyle. Health education is one way to increase knowledge that will affect a person's attitude. The purpose of this study was to determine the level of knowledge and attitudes before and after counseling about Healthy Lifestyles in students of SD Negeri 13 Blang Mangat. This research is a quasi-experimental research with a total sample of 52 people. The sampling technique used was total sampling. Measurements were made using a questionnaire consisting of knowledge and attitudes about Healthy Lifestyle. The results of this study indicate that the majority of respondents before the counseling had a low level of knowledge, namely 40.4%, and increased to good as much as 84.6% after being given counseling. The majority of students' attitudes before counseling were carried out were 51.9% enough and increased to good as much as 53.8% after counseling. Data analysis using the Wilcoxon test. The results of statistical analysis showed p value <0.05. This study concludes that there are differences in the level of knowledge and attitudes of students before and after being given counseling about Healthy Lifestyle at SD Negeri 13 Blang Mangat.